Aspecte actuale ale raportului venituri - nivel minim de trai în România - Barbu, Gheorghe; Ghimpău, Vasilica (Calitatea Vieții, 1993)
As a reflection of the state of economy, the relation between the population’s income and poverty level in Romania has been suffering a degradation more and more unbearable for certain categories of families. Highligthing this process, the study takes into account the unfavourable modifications of this relationship of the retires with underaveraged pensions; in many circumstances, the incomes have reached the point where they are situated not only under the decent poverty level, but even under the subsistence level. In the case of children-endowed employees families there’s one more factor which leads to such a reality, that is the unarticulated evolution (related to the incomes and mostly to the price-index) of the nominal allocation.